(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
Artificial Intelligence (AI) has emerged as a transformative force with the potential to revolutionize various sectors, including governance and state development. This paper explores the significance of AI in the context of state development, discussing its impact on economic growth, public services, decision-making processes, and societal well-being. By examining case studies and expert opinions, this paper provides valuable insights into the importance of integrating AI technologies for sustainable state development in the contemporary world.